The Islamic Worldwide And Civilization - Solihu, Abdul Kabir Hussain (s.n, 2012)
Modern civilization has brought many unprecedented achievements in science and technology but has equally generated a wide array of complicated issues which have been addressed from different perspectives. The absence or marginalization of the Divine-inspired civilizational worldview, the true vision of reality and the meaningfulness of existence has led to the deterioration of the quality of life, the degeneration of social order and the erosion of religious values. This book contains chapters that cut across several disciplines addressing social, psychological, political, environmental, developmental, medical, communicational and conceptual issues from the ethico-religious perspective. It deals with the Islamic vision of progress and development and its solution to human predicaments. The book addresses the centrality of morality to human nature and the role of religious ethics in coping with challenges brought about by modern secular civilization. It also introduces the Islamic perspective of killing, either for a suspected terror motivation or for a supposedly mercy